Sleep, jet lag and performance - Mahoney, C. E. (The science of figure skating, 2018)
Sleep duration and quality are critical components ofrecovery, optimal health, and performance. A lack of sleep (either SD or SR) results in performance decrements in a variety of physiological metrics tliat can directly impair figure skating performance. Therefore, maintaining consistent sleep hygiene ( e.g., adequate sleep duration, appropriate sleep onset/wake time, etc.) is important for tlie daily training environment, longer-term training adaptations (Jacoboski, Mahoney, & VanHeest, 2017), and ultimately competitive performance outcomes. The transmeridian travel often required for figure skating will result in jet lag and possible performance decrements if left unaccounted. Implementing pre-travel strategies to advance or delay the circadian rhythm to match the competition time zone can help skaters minimize jet lag symptoms. Ultimately, the day-to-day training as weil as competition performances will benefit from proper sleeping pattems and appropriate adjustments to the circadian rhythm.